ABORDAGEM CRÍTICA SOB A ÓTICA DA AÇÃO COMUNICATIVA DE HABERMAS: GESTÃO PARTICIPATIVA NO CAMPUS SERRA DO IFES - Eglalciane Lyrio Tongo Castro (Universidade Federal de Santa Catarina, 2018)
This study aimed to understand, critically, as is characterized the participative management on IFES – Campus Serra, from the understanding and the interactive process of the administrative technicians staff (TAEs) classes C, D and E and immediate supervisors. Thus, Jürgen Habermas's Communicative Action Theory (CAT), as well as its proposal for democracy deliberative, were undertaken as a theoretical framework for understanding this process. This work is characterized as a qualitative research and has a critical approach with dialectical view of social reality. Empirical data were produced by desk research, participant observation and semi-structured interviews. The content analysis was used for the treatment of interview. The results point to the construction of participatory actions of instrumental nature, established based on the interests of the management of specific and individual groups. Thus, the practice of participative management is characterized as a strategic space to reach the success and not the understanding, where the TAEs share the responsibility in the process of maintenance and construction of the phenomena that hamper the development of democratic participation.